Screening of Pediatric Facial Fractures by Brain Computed Tomography: Diagnostic Performance Comparison With Facial Computed Tomography. Issue 3 (March 2020) - Ryu, JongChan; Yun, Seong Jong; Lee, Sun Hwa; Choi, Yoon Hee
Abstract : Objectives: Facial bone fractures secondary to head trauma are more common in children than in adults. Recently, multidetector row computed tomography (CT) has been considered superior to conventional radiography. Some studies have reported that facial soft tissue injuries require both facial and brain CT and that brain CT is helpful in screening facial bone fractures. However, these studies included only adult patients. The aim of this study was to evaluate the diagnostic performance of brain CT and the need for additional facial CT to detect facial bone fractures in emergency pediatrics. Methods: This multicenter study was conducted retrospectively in 2 tertiary hospitals in Seoul, Republic of Korea. The data were collected from the medical records of pediatric patients younger than 8 years who had undergone both brain and facial CT on the same day in the emergency department. All CT scans were retrospectively and independently evaluated by 1 board-certified radiologist and 1 board-certified emergency medicine physician. A P value of <0.05 was considered statistically significant. Results: Sensitivity was 92.31%, specificity was 100%, positive predictive value was 100%, negative predictive value was 99.31%, and accuracy was 99.36% for the emergency physician; all parameters were 100% for the radiologist. Conclusions: Brain CT showed high diagnostic performance to detect facial bone fractures with high accuracy in pediatric patients. As emergency physicians, we should consider facial bone fractures when reviewing brain CT images of pediatric patients with blunt head and face trauma.